2005
DOI: 10.1017/s1461145704004717
|View full text |Cite
|
Sign up to set email alerts
|

Hypericum extract in patients with MDD and reversed vegetative signs: re-analysis from data of a double-blind, randomized trial of hypericum extract, fluoxetine, and placebo

Abstract: Hypericum extract (HE) might be favourably active in depressed patients with reversed vegetative signs (RVS). Therefore, we performed an exploratory subgroup analysis of a three-armed study to compare HE, fluoxetine, and placebo in patients with major depressive disorder (MDD) in a 12 wk trial. A total of 135 patients were randomized to 12 wk treatment with HE LI 160 (900 mg/d), fluoxetine (20 mg/d), or placebo. Patients with RVS were defined in two steps, according to DSM-IV. First, patients with melancholy-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…21,22 Many foreign studies on Hypericum perforatum extract showed that the drug has an antidepressant effect and is especially suitable for patients with mild-to-moderate depression. 2330 Consistently, our study proved the Shugan Jieyu capsule has a definite curative effect in treatment of acute MI patients with depression.…”
Section: Discussionsupporting
confidence: 80%
“…21,22 Many foreign studies on Hypericum perforatum extract showed that the drug has an antidepressant effect and is especially suitable for patients with mild-to-moderate depression. 2330 Consistently, our study proved the Shugan Jieyu capsule has a definite curative effect in treatment of acute MI patients with depression.…”
Section: Discussionsupporting
confidence: 80%
“…A study in patients with mild to moderate depression comparing the effect of hypericum extract LI 160 with fluoxetine and placebo (48) found a significant superiority of hypericum compared with fluoxetine and a trend to a superiority compared with placebo. Interestingly, a subgroup analysis including patients with reversed vegetative signs, but after the exclusion of melancholic features, found the same pattern in this subgroup with a much more pronounced effect size, but no efficacy of any drug compared with placebo in the non‐atypical patients (49). Open studies demonstrated the efficacy of hypericum in seasonal affective disorder (SAD) (50–52), which is a subgroup of AD with fatigue as one main symptom.…”
mentioning
confidence: 76%
“…Four studies demonstrated that SJW had similar (Behnke et al, 2002;Bjerkenstedt et al, 2005) or superior Schrader, 2000) effects to fluoxetine. An analysis of the sub-sample of a 12-week 3-arm study discovered that SJW (LI 160 900 mg/day) ameliorated depression-based vegetative presentations, while fluoxetine (20 mg/day) was statistically equivalent to placebo (Murck et al, 2005). A 2006 study found lower remission rates for SJW in comparison with fluoxetine, although intention-to-treat analysis (ITT) showed no difference between the groups (Moreno et al, 2006).…”
Section: Major Depressive Disorder (Mdd)mentioning
confidence: 99%